The initial visibility of updated recommendations on preseason heat safety in high school athletics among United States athletic trainers. - Zachary Yukio Kerr; Jake C Diana; William M Adams; Johna K Register-Mihalik; Aliza K Nedimyer (PLoS ONE, 2024)
Updated recommendations on preseason heat safety in high school (HS) athletics ("2021 Consensus Statements") were published in April 2021. This cross-sectional survey study explored the initial roll-out of the 2021 Consensus Statements, including their visibility among United States HS athletic trainers (ATs) and perceived levels of confidence in implementing them. Recruitment occurred first, from a random selection of ATs from the Board of Certification, Inc., and second, an open invitation via social media. An online cross-sectional questionnaire had participating ATs note whether they had seen the 2021 Consensus Statements. If yes, ATs reported their perceived level of confidence in implementing them (5-point-ordinal scale from "not at all confident" to "very confident); if no, ATs disclosed (open-ended) why they had not yet seen them. Descriptive statistics were calculated for quantitative variables; template analysis identified codes related to visibility of and confidence in implementing 2021 Consensus Statements. Nearly half (45.7%) of 116 responding HS ATs reported having seen at least one 2021 Consensus Statements; 23.3% had reviewed all three. Common reasons among the 63 that had not seen them included: not aware they were published (n = 22), have yet to read them (n = 19), and believed they could not access the journal (n = 10). Of the 53 ATs having seen at least one of the 2021 Consensus Statements, 67.9% (n = 36) were very/fairly confident in implementing them at their HS. Reasons for confidence included their schools ensuring up-to-date EHI prevention and management practices (n = 18) and athletics constituent support (n = 8). This exploratory study observed proportions of surveyed HS ATs that had not seen the 2021 Consensus Statements and were not confident in implementing them. Findings highlight the need to continue improving messaging about access to best-practice recommendations. Further, continued efforts inclusive of active and passive dissemination strategies across all athletics constituents are needed to aid proper implementation.